Durability of Polymer Metal Multilayer: Focus on the Adhesive Chemical Degradation - Dubelley, Florence; Bas, Corine; Planes, Emilie; Pons, Emmanuelle; Yrieix, Bernard; Flandin, Lionel (Frontiers in Chemistry, 2018)
Mechanical toughness and high barrier to air and water may be combined in a polymer-metal multilayer film, provided that the two materials are properly bonded together. Delamination is indeed the most severe flaw observed in service. This suggest that the polyurethane (PU) adhesive at polymer-metal interface failed at bearing the shear forces, it happens principally if the system is submitted to elevated temperature and humidity. Raman microscopy reveals a cohesive delamination, with glue on either surfaces after rupture. A detailed investigation of the kinetic of degradation of the polyester was therefore carried out. IR spectroscopy of standalone PU film hydrolyzed in a controlled manner furnished a series of aging markers. The reference curve was established for about a year in continuous severe aging conditions. This curve could be further used to compare the amount of degradation in real systems in a wide range of condition and time. Moreover, at the metallized interphase, a complex with free hydroxyl group was detected. The content of this AlIII complex based on terephthalate or carbamate was a function of ester hydrolysis progress in the layer.